Isolation of human immunodeficiency virus-related simian immunodeficiency viruses from African green monkeys. - Kraus, G (1989)
We have isolated lentivirus strains that are related to the human immunodeficiency virus (HIV) from African green monkeys (Cercopithecus aethiops; AGM). Although immunologically related, these SIVagm are clearly distinct from other simian immunodeficiency virus (SIV) isolates, including isolates from Macaca mulatta (SIVmac) or even from other AGM. The SIVagm strains described in this communication grow well in a limited number of human T-lymphoma lines. Virus density, morphology, and reverse transcriptase activity are characteristic of the lentivirus group. SIVagm exhibits the following pattern of major virus proteins: p18, p28, gp45, p64, gp140. They appear to bind to the target cell via the CD4 or its primate analogue. Four virus isolates have already been molecularly cloned for detailed genomic analysis and within this SIV agm group they exhibit the genomic variability that is typical of lentiviruses. AGMs infected with this virus apparently remain healthy and therefore SIVagm not only provides a virus model for vaccine studies but also allows investigation of the defense mechanisms (immunological and others) that keep the AGMs healthy. Furthermore, precise genomic analysis of these and other SIV strains will lead to a better understanding of the evolution and pathogenicity of human lentiviruses like HIV.